The impact of radiotherapy on disease control in vulvar extramammary Paget’s disease: a retrospective study from a single institution - Seol, Aeran; Kim, Se Ik; Song, Yong Sang (Frontiers in Oncology, 2025)
ObjectiveVulvar extramammary Paget’s disease (EMPD) is a rare intraepithelial carcinoma that affects apocrine gland-bearing skin, predominantly in postmenopausal women. Due to its rarity, optimal treatment strategies, including the role of radiotherapy (RT), remain poorly established. This study aimed to evaluate the role of radiation therapy in vulvar EMPD, focusing on preserving functional and aesthetic vulvar tissue without compromising survival rates.Materials and methodsWe conducted a retrospective cohort study of 32 patients diagnosed with vulvar EMPD at Seoul National University Hospital between 2000 and 2024. Clinicopathologic data, including demographics characteristics, clinical presentations, histopathological findings, treatment modalities, and outcomes, were collected. Patients were divided into two groups: those who received neoadjuvant or adjuvant RT (n = 9) and those who did not (n = 21). Univariate and multivariate analyses were performed to assess factors related to recurrence and progression-free survival (PFS).ResultThe median age at diagnosis was 63.8 years (range: 38.0–87.8), with 84.4% of patients being postmenopausal. Among the 32 patients, 30 (93.8%) underwent surgery, and nine (28.1%) received adjuvant RT. Recurrence rates were similar between the RT (66.7%) and non-RT (66.7%) groups. The median PFS was longer in the RT group (28.1 months) compared to the non-RT group (23.4 months), although this difference was not statistically significant (p = 0.395). Univariate and multivariate analyses identified age ≥ 60 years as a borderline predictor of poorer PFS (p = 0.053), while no significant associations were found between RT and postoperative complications or recurrence risk.ConclusionIn conclusion, although RT did not show a statistically significant survival benefit, both our data and previous studies strongly suggest that RT holds potential for disease control. It may be the primary treatment before and after surgery in patients with extensive vulvar EMPD.